2020
DOI: 10.18633/biotecnia.v22i3.969
|View full text |Cite
|
Sign up to set email alerts
|

Efecto de la variedad y fecha de siembra en el potencial productivo de remolacha azucarera

Abstract: La remolacha azucarera es un cultivo tradicionalmente de zonas templadas, aunque el desarrollo de nuevas variedades, permite su explotación en regiones tropicales y subtropicales. Sin embargo, para obtener buenos rendimientos y alta calidad, es fundamental evaluar variedades y fechas de siembra antes de su establecimiento. El objetivo de este estudio fue evaluar el potencial productivo de tres variedades de remolacha azucarera (Coronado, Syngenta y SesVanderHaven) en dos fechas de siembra en el Campo Experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…As a result, in the last decade, the potential to grow and harvest sugar beet for bioethanol production in the northwest semi-desert regions of Mexico has been explored, generating SBW. For instance, Jimenez-Leon et al [6] evaluated the productive potential of three sugar beet cultivars; Cadet, Coronado large, and SV MEI in two sowing dates in the experimental field of the University of Sonora (Coordinates: 29 • _00 48" NL, 111 • 08 07" WL and 151 MASL (meters above sea level)), under split-plot design. Authors reported that Coronado's large cultivar sowing in November had the highest tubers production (109.2 t•ha −1 ) and highest total soluble solids content (19.3 • Brix), while the highest foliage production (25.4 t•ha −1 ) in dry weight was obtained in Coronado's large cultivar sowing in October.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, in the last decade, the potential to grow and harvest sugar beet for bioethanol production in the northwest semi-desert regions of Mexico has been explored, generating SBW. For instance, Jimenez-Leon et al [6] evaluated the productive potential of three sugar beet cultivars; Cadet, Coronado large, and SV MEI in two sowing dates in the experimental field of the University of Sonora (Coordinates: 29 • _00 48" NL, 111 • 08 07" WL and 151 MASL (meters above sea level)), under split-plot design. Authors reported that Coronado's large cultivar sowing in November had the highest tubers production (109.2 t•ha −1 ) and highest total soluble solids content (19.3 • Brix), while the highest foliage production (25.4 t•ha −1 ) in dry weight was obtained in Coronado's large cultivar sowing in October.…”
Section: Introductionmentioning
confidence: 99%